Acoustic analysis of esophageal speech in patients after total laryngectomy - Wszołek, Wiesław; Modrzejewski, Maciej; Przysiężny, Monika (Archives of Acoustics, 2007)
Laryngeal cancer is one of the most frequent types of malignant tumor in male patients andit is located at position 5 among all the malignant tumors. The primary method of laryngealcarcinoma treatment for the cases with advanced cancer stages is the surgical treatment. Insuch a treatment the most frequent version is the total extraction of the organ. An effectivepostoperative therapy leads to the extension of the patients life-time, but the price is a seriousdisability, considerably impairing the patients communication with other persons. Thereforethere is a problem of creation of a substitute voice and speech for those patients. The creationmechanism of the esophageal speech is the formation of vibration generator in the upper partof oesophagus. The substitute air container is formed by the oesophagus itself and the airvibrations in the upper part of oesophagus, generated during the anti-peristaltic motion of theair removed from oesophagus, create the primary pitch. The modulation of the fundamentalpitch is obtained by the unchanged articulation organs and resonance cavities of the body.In the present paper an acoustic study of esophageal speech is described. An attempt hasbeen made to determine the acoustic signal parameters, which can be useful in evaluation ofesophageal speech quality.